ANTROPOLOGI BUDAYA SUNDA DALAM KITAB TAFSIR AL-QURAN BERBAHASA SUNDA (KAJIAN TAFSIR RAUDHATULIRFAN FI MA’RIFAT AL-QUR’AN) - Hermawan, Moch. Raffif Zulfan; Hermawan , Moch Raffif Zulfan; Kiki Muhamad Hakiki; Masruchin (MADINAH, 2025)
This study is based on the importance of the relationship between local culture and the interpretation of the Qur'an, particularly in the context of Sundanese culture. This research aims to examine how Sundanese cultural values are adapted in the interpretation of the Qur'an and how this interpretation contributes to the preservation of local culture. This study employs a qualitative approach with a literature study method to analyze the relationship between interpretation and Sundanese culture through the perspective of cultural anthropology. The findings indicate that Ahmad Sanusi’s interpretation not only serves as a medium for Islamic preaching but also plays a role in preserving Sundanese culture. These are three strategies: tahmil, tahrim, and taghyir; this is reflected in the use of the Sundanese language, the undak-usuk basa (language hierarchy) system, and social values such as silih asah, silih asih, and silih asuh (mutual sharpening, mutual caring, and mutual nurturing). Additionally, Ahmad Sanusi incorporates local cultural elements, such as tawasul and wayang golek performances, as relevant preaching media for the Sundanese community. Thus, the interpretation of the Qur'an not only serves as an explanation of the sacred text but also as part of a cultural heritage that reflects local identity, proving that Islamic teachings can harmonize with local wisdom without losing their universal values